Dominant height curves and local site index for Samanea saman plantations in Liberia, Guanacaste, Costa Rica. - Mora-Chacón, Fernando (2022)
[Introduction]: Long-term research on the growth and timber yield of plantations with forest species native to tropical dry forest is scarce, even though many of these species have real potential for commercial timber production. [Objective]: To create a productivity classification system based on dominant height growth and local site index curves for Samanea saman to facilitate technical management work for this native species in the tropical dry forest of Liberia, Costa Rica. [Methodology]: The dominant height-age data used to construct the dominant height and site index curves were obtained from permanent plots, which were measured annually for 21 years. Eight regression models used throughout forestry literature were tested. The models were statistically evaluated and the estimated values ​​were plotted against the observed values in order to graphically analyze the fit of the data. [Results]: The most satisfactory model was that of Prodan (1951) with R2adj of 93.72%, MSE = 3.9706, SEE = 1.9926 and EMA = 1.4830 for a P-value of (0.00001) at a confidence level of 95%. The average curve adjusted by the Prodan model, at first presents a slope that suggests a rapid initial growth, with a first section of the curve that rises rapidly until the age of 8 years; then, a second section between the ages of 9 and 14, where it continues to grow at a lower rate. [Conclusions]: The Prodan model presented the best fit. The proposed productivity classification system employed 15-year tree age as the base age to construct the curves that correspond to site indices 9, 12, 15, and 18, which cover the entire observed site quality range.